Impact of crude oil price, exchange rates and real GDP on Malaysia's food price fluctuations: symmetric or asymmetric? - Wong, Kelly Kai Seng; Shamsudin, Mad Nasir (Faculty of Economics and Management, Universiti Putra Malaysia, 2017)
In this study, we examined the impact of crude oil price, real GDP, and exchange rates on Malaysian food price fluctuation by using the quarterly data from quarter 1 of year 2000 to quarter 2 of year 2016. Considering the possibility that an asymmetric impact exists between the underlying variables, an asymmetric Unrestricted Non-linear Auto-Regressive Distributed Lag (NARDL) model was adopted. In short, the bounds test for cointegration showed that the underlying variables have a significant long-run relationship along with changes in food prices. However, only the crude oil price has a symmetric long-run effect on the food price fluctuation. On the other hand, the real GDP and exchange rates have an asymmetric long-run effect on food price movements. In the short-run, the crude oil price has an insignificant impact on food price volatility, but the growth of real GDP and exchange rates have a significant impact on food price changes. Hence, this study suggests that policymakers should be taking the exchange rate factor instead of crude oil price into consideration.